Magnetic Resonance Imaging Evaluation of Wolffian Duct Anomalies - OHVIRA and OSVIRA - Lukshay Bansal; Suryansh Arora; Akhila Prasad (Wolters Kluwer Medknow Publications, 2024)
Herlyn-Werner-Wunderlich syndrome in females, also known as obstructed haemivagina and ipsilateral renal agenesis (OHVIRA), and Zinner's syndrome, also known as OSVIRA in males, are two rare congenital syndromes affecting the urogenital tract. OHVIRA is obstructed haemivagina and ipsilateral renal agenesis and OSVIRA abbreviation stands for obstructed seminal vesicle and ipsilateral renal agenesis. For a long, these syndromes were considered different entities, owing to our poor understanding of underlying embryopathogenesis; however, in light of the recent acceptance of the Wolffian origin of the vagina in its entirety, these two syndromes are considered to be cut from the same cloth. In this case series, we present magnetic resonance imaging features of two cases each of OHVIRA and OSVIRA and discuss the similarities in embryopathogenesis behind them while debunking the old concepts. A deep understanding of embryopathogenesis allows a clinician and radiologist to predict the disease manifestation, and its outcome and also acts as a guide to screen for potential subtle defects, which would otherwise have been missed.